Identification and Screening of Phosphate Solubilizing Aspergillus Species Isolated from Soil in the Three Southern Border Provinces of Thailand - Chitphithak, Ithipon; Kaewchai, Saithong; Pornsuriya, Chaninun (Princess of Naradhiwas University Journal, 2020)
Fungi of the genus Aspergillus have great importance in ecological systems. This research was conducted to identify Aspergillus spp. isolated from soil in Narathiwat, Pattani, and Yala provinces and screen phosphate solubilizing strains. Forty-three species of Aspergillus spp. were isolated from soil by tenfold serial dilution method, and potato dextrose agar (PDA) pour plate metthod. All isolates were identified, based on morphological characters and nucleotide sequence of the internal transcribed spacers (ITS) and distributed into 7 species, namely: A. aculeatus, A. alabamensis, A. carbonarius, A. clavatus, A. japonicus, A. niger and A. terreus. Phosphate solubilizing ability of Aspergillus spp., isolated from soil, was screened by halo zone test on Pikovskaya’s agar medium. The result revealed that A. alabamensis and A. carbonarius were able to solubilize phosphate in vitro.